Design of Video Quality Metrics with Multi-Way Data Analysis A data driven approach - Keimel, Christian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book proposes a data-driven methodology using multi-way data analysis for the design of video-quality metrics. It also enables video- quality metrics to be created using arbitrary features. This data- driven design approach not only requires no detailed knowledge of the human visual system, but also allows a proper consideration of the temporal nature of video using a three-way prediction model, corresponding to the three-way structure of video. Using two simple example metrics, the author demonstrates not only that this purely data- driven approach outperforms state-of-the-art video-quality metrics, which are often optimized for specific properties of the human visual system, but also that multi-way data analysis methods outperform the combination of two-way data analysis methods and temporal pooling. .
Introduction -- Video Quality -- Video Quality Metrics -- Data Analysis Approach -- Two-way Data Analysis -- Multi-way Data Analysis -- Model Building Considerations -- Designing Video Quality Metrics -- Performance Comparison -- Conclusion.
Keywords: Signal processing; User interfaces (Computer systems).; Human-computer interaction; Telecommunication; Signal, Speech and Image Processing; User Interfaces and Human Computer Interaction; Communications Engineering, Networks